THE IMPLEMENTATION OF CHRISTIAN MORAL CONCEPTS IN THE SOCIAL INTERACTION BEHAVIOUR OF STUDENTS OF STIPAS ARCHDIOCESE OF KUPANG - Masan, Valentinus Kopong (Postgraduate School, Universitas Nusa Cendana, 2024)
This paper presents an analysis of the application of Christian morality in social interactions among students, lecturers, employees, and the community at the STIPAS Campus of the Archdiocese of Kupang. The research aims to serve as a reflection for promoting positive changes in students' development in the future. The study adopted a qualitative and descriptive quantitative approach and was carried out from September to December 2023. The application of Christian morality was assessed based on the fruits of the spirit outlined in Galatians 5:22-23, including love for others, joy, peace, patience, kindness, goodness, loyalty, trustworthiness, honesty, reliability, and gentleness. The research showed that the overall score for the application of Christian morality was 3.8 out of 5. To enhance the application of Christian morals, STIPAS has implemented various measures such as socializing academic and student guidelines, changing teaching methods, involving more students in activities, providing routine assistance from student affairs, and enforcing sanctions. These findings stress the importance of STIPAS students, particularly those aiming to become Catholic Religion teachers, adopting Christian morals in their lives.